ACADEMIC WRITING TRAINING USING THE APPLICATION LONGMAN DICTIONARY OF CONTEMPORARY ENGLISH FOR TEACHERS OF SMPN 1 TELUKJAMBE EAST KARAWANG - Krishnapatria, Kriswanda (LPPM Univ. Ibn Khaldun Bogor, 2023)
This training is an endeavor to share knowledge and experience for teachers of SMPN 1 Telukjambe Timur, Karawang to use and utilize the Longman Dictionary of Contemporary English (LDOCE) program according to their individual needs, especially for writing academic purposes (publications on the journal). This activity is also expected to help participants obtain additional media and references in carrying out their roles. This training activity focused on introducing scientific papers and their structure, the LDOCE application and its features, and the use of LDOCE for independent academic writing. The methods used in this training include lectures, discussions, and mentoring practices. After carrying out this activity, it can be concluded that this training helps maintain teacher motivation in working and honing academic writing skills through an application on a computer.